Neuraminidase activity is not the cause of influenza virus-induced neutrophil dysfunction. - Abramson, J S (1985)
Influenza viruses have been shown to decrease the ability of polymorphonuclear leukocytes (PMN) to respond to a variety of stimuli. This study was done to determine if viral neuraminidase was responsible for decreased PMN function. Treatment of human PMN with purified neuraminidases from influenza virus, Vibrio cholerae, or Clostridium perfringens did not significantly affect the ability of human PMN to respond to stimulation. Occasional virus preparations that lacked the ability to depress PMN function did not differ in neuraminidase activity from viruses capable of causing depression. These results demonstrate that neuraminidase activity is not the cause of influenza virus-induced PMN dysfunction.